Papillary Renal Cell Carcinoma in Transplanted Kidney and Xp11.2 Translocation/ Transcription Factor E3-Rearranged Renal Cell Carcinoma in the Native Kidney: A Case Report - Min Hye Kim; Kyeong Ah Kim; Jeong Woo Kim; Seok Young Lee; Jae Woong Choi (Journal of the Korean Society of Radiology, 2024)
Concomitant renal cell carcinomas (RCC) of both native and allograft kidneys are extremely rare, and only a few cases have been reported in the available English literature. A particularly rare variant within the adult population is the Xp11.2 translocation/transcription factor E3 (TFE3)-rearranged RCC. Although few case reports of TFE3-rearranged RCC have been reported in children who underwent kidney transplantation (KT), no case of adults with TFE3-rearranged RCC following KT has been reported. Herein, we presented the radiological and pathological findings of a rare metachronous papillary RCC in the allograft kidney and TFE3-rearranged RCC in the native kidney. The TFE3-rearranged RCC in the native kidney exhibited slow expansion in size over five years. Radiologically, it appeared as a slightly enhanced, lobulated mass on contrast-enhanced CT. MRI revealed high signal intensity on T1-weighted images and low signal intensity on T2-weighted images.